Kepastian Hukum Akta Di Bawah Tangan dalam Perspektif Kewenangan Notaris - Dahlang Dahlang (Institut Agama Islam Negeri (IAIN) Kendari, 2016)
The Republic of Indonesia as a state of law based on Pancasila and the Constitution of the Republic of Indonesia Year 1945 to ensure certainty, order, and the protection of the law, with a core of truth and justice. Assurance, public order and the protection of law in society requires legal basis has the strongest strength of evidence and perfect. The legal guarantee should be felt by all the people of Indonesia but in practice can not walk properly because of the legal policy of Constitution No. 30 of 2004 concerning Notary Jo. Law No. 12 of 2014 on the Amendment of Constitution No. 30 of 2004 About the Notary who should be able to guarantee legal certainty under the deed of the hand, but until now not be able to realize the legal certainty for the community.